A influência da inovação disruptiva digital no desempenho dos processos de mapeamento e atração de executivos de tecnologia - Pigola, Angélica (2021)
Dynamic capabilities (DC) influence the ability of digital platforms to take advantage of innovation opportunities by responding to existing disruption threats, linking products and services to the underlying knowledge at a given time and over time (Helfat & Raubitschek, 2018). These capabilities, in turn, place digital ecosystems in an even stronger position to address the challenges of digital disruptive innovation (DDI). The mapping process and the attraction of technology executives directly impacts this environment in this most relevant asset: the technology executive. Therefore, we tried to verify to what extent the DDI influences the performance of the processes of mapping and attracting executives in technology in specialized consultancy in recruitment and selection (SCRS). We seek to highlight the presence of DC in reaction to DDI, in this context, in the light of recent scientific studies and to study the effects of the performance of the processes of mapping and attraction of technology executives, regarding the use of digital platforms and their impacts on the number of services provided and online revenue generation. The research presents in three phases, being the first a systematic literature review, the second a quantitative approach with SCRS based in Brazil, and the third, a technological service patents analysis of high analytics information technologies (HAI). In the first phase, we followed Snyder’s (2019) methodological recommendations for a systematic literature review. In the second phase, we collected the data through a questionnaire (survey) with questions extracted from validated scales and addressed to specialized professionals of the studied companies. The profile of respondents concentrates at the level of specialists, managers, and directors since they have access to strategic information, qualifying these professionals as respondents. For the analysis of the results, we used the statistical technique of confirmatory factor analysis and PLS-SEM which allows estimating the probability associated with the occurrence of a certain event in view of a set of explanatory variables. In the third phase, we identified emerging digital technologies of high analytics information (HAI), through the analysis of technological routes and observation of technological cooperation among holders, obtained by analysis of social networks (ASN) methodology. Based on evaluation and analysis of their own DC, organizations can identify appropriate roles in the development of digital platforms that lead to DDI, considering dependent path between available intellectual structure and technical architecture of digital platform (Hein et al., 2020). As a theoretical contribution, we present a theoretical and dynamic integrating model, expanding knowledge and understanding of relevant strategies in reaction to DDI. As a practical contribution, we highlight the presence of efforts in the application of DC in support of development of digital platform capacity, reinventing its main activities. Associating with operating in open markets and global competition, as is the case of SCRS market segment, a common tendency to escape of zero profit requires essential capabilities, resources, and strategies. This analysis may be applied equally to other types of ecosystems.